Binaural fusion test as an alternative to masking in pure-tone air-conduction audiometry - Dattatreya Narahari (Journal of All India Institute of Speech and Hearing)
The Binaural fusion tests and conventional air-conduction tests were administered to 33 normal subjects and 100 pathological cases consisted of 4 groups : 1. Conductive loss group; 2. Mixed loss group ; 3. Sensori-neural lo.ss group ; and 4. Unilateral total· loss group.